PENGARUH KEPEMIMPINAN BERBASIS AJARAN ASTHA BRATA DAN EFIKASI DIRI PADA KOMITMEN AFEKTIF - , Wahyu Jati Anggoro, Prof. Djamaludin Ancok, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aim of this study was to understand the effect of leadership based on Astha Brata and general self-efficacy toward affective organizational commitment. Leadership scale based on Astha Brata teaching was constructed and evaluated during the pre-eliminary study. Research subjects involved are permanent employees at Grand Quality Hotel Yogyakarta (N = 57). Path analysis was used to determine the prediction coefficient of leadership based on Astha Brata and self-efficacy toward affective commitment. The result shows that leadership based on Astha Brata dimension (self-confident Î² = 0.38, Î² = 0.38 interactive, firmness Î² = 0.18) and general self-efficacy (Î² = 0.26) was positively predict affective organizational commitment. The variance explained by the model was 54,4%. Further result will be discussed.